Functional Analysis of the PgCesA3 White Spruce Cellulose Synthase Gene Promoter in Secondary Xylem - Sena, Juliana Stival; Lachance, Denis; Duval, Isabelle; Nguyen, Thi Thuy An; Stewart, Don; Mackay, John; Séguin, Armand (Frontiers in Plant Science, 2019)
Cellulose is an essential structural component of the plant cell wall. Its biosynthesis involves genes encoding cellulose synthase enzymes and a complex transcriptional regulatory network. Three cellulose synthases have been identified in conifers as being potentially involved in secondary cell wall biosynthesis because of their preferential expression in xylem tissues; however, no direct functional association has been made to date. In the present work, we characterized the white spruce (Picea glauca (Moench) Voss) cellulose synthase PgCesA3 gene and 5’ regulatory elements. Phylogenetic analysis showed that PgCesA1-3 genes grouped with secondary cell wall-associated Arabidopsis cellulose synthase genes, such as AtCesA8, AtCesA4, and AtCesA7. We produced transgenic spruce expressing the GUS reporter gene driven by the PgCesA3 promoter. We observed blue staining in differentiating xylem cells from stem and roots, and in foliar guard cells indicating that PgCesA3 is clearly involved in secondary cell wall biosynthesis. The promoter region sequence of PgCesA3 contained several putative MYB cis-regulatory elements including AC-I like motifs and secondary wall MYB-responsive element (SMRE); however, it lacked SMRE4, 7 and 8 that correspond to the sequences of AC-I, II and III. Based on these findings and results of previous transient trans-activation assays that identified interactions between the PgCesA3 promoter and different MYB transcription factors, we performed electrophoretic mobility shift assays (EMSA) with MYB recombinant proteins and cis-regulatory elements present in the PgCesA3 promoter. We found that PgMYB12 bound to a canonical AC-I element identified in the Pinus taeda PAL promoter and two AC-I like elements. We hypothesized that the PgMYB12 could regulate PgCesA3 in roots based on previous expression results. This functional study of PgCesA3 sequences and promoter opens the door for future studies on the interaction between PgMYBs and the PgCesA3 regulatory elements.